Determinants of infant nutrition status in rural farming households before and after harvest. Issue 3 (29th April 2019) - Muhimbula, Happiness; Kinabo, Joyce; O'Sullivan, Aifric
Abstract: Infant and young child feeding (IYCF) practices determine infant growth, development and health. Despite global recommendations for exclusive breastfeeding until 6 months, adherence rates are low worldwide for different reasons, largely dependent on environment. In low‐income countries, inappropriate IYCF leads to poor nutrition status. This study examined IYCF practices and nutrition outcomes in rural farming households in Tanzania before and after harvest. Mothers and their infants were recruited from two regions in Tanzania. Demographics, health status, IYCF practices, anthropometrics and haemoglobin were measured; preharvest and postharvest. Regression analysis modelled the relationship between IYCF and nutrition outcomes. Despite high rates of breastfeeding a large proportion did not meet early initiation of breastfeeding and minimum acceptable diet standards. Undernutrition was high with 30–40% of infants classified as stunted depending on season, and the majority (81%) were anaemic. Early initiation of breastfeeding was associated with higher Length‐for‐age z ‐score and weight‐for‐age z ‐score and lower risk of stunting and underweight ( p < 0.05). The introduction of fluids other than breast milk in the first 3 days after birth was associated with lower weight‐for‐age z‐score and increased underweight ( p < 0.05). Maternal age and height were strongly and positively associated with child anthropometrics. Findings confirm the importance of early infant feeding practices for growth and development and emphasize the significance of mother's nutrition status in relation to infant health. Future interventions should focus on improving maternal nutrition status before, during and after pregnancy as well as educating and supporting mothers to adopt appropriate infant feeding including breastfeeding practices for the prevention of undernutrition.